Chest trauma: introduction - Campos Pierri, Néstor; Bertullo, Hugo; Bonilla, Conrado; Chifflet, Juan; di Leoni, Francisco; Estable, Héctor; Tamborindeguy, Luis; Gnazzo, Jorge (Cirugía del Uruguay, 1990)
An update on this is presented at the Roundtable on Thorax Trauma Extensive topic that interests several specialists in Medicine.